The Problematic Nature of Periodization and the Alleged Paradigm Shifts: Courtly Love Poetry (Minnesang), Petrarch’s Sonnets, Goethe’s Erotic Compositions, and Brecht’s Dreams of Love - Classen, Albrecht (Global Journal of Cultural Studies, 2023)
This study raises the scepter regarding the heuristic value of literary periodization and hence also of the concept of the paradigm shift. Undoubtedly, throughout time, changes in the cultural epochs took place, and we can easily determine larger cultural, material, technical, political, and religious transformations Hence the genre of literary histories that inform us in a concise and authoritative manner about that phenomenon. By the same token, however, we might be forced to realize that many of those changes taking place from period to period affected more the form and the text-external references and less the idealistic concern by the individual poets. To illustrate this phenomenon, here I trace a long-term discourse on love from the Middle Ages to the twentieth century to identify a fundamental trope that resisted all paradigm shifts and proved to have a universal staying power beyond all measures. Although value systems and social-economic conditions underwent profound changes from the past to the present, the human dimension itself was apparently quite resistant to those transitions, as the topic of love confirms from the earliest time until today.